Quick Assessment of Landslide Potential Using Satellite Imagery in Bili-Bili Reservoir Catchment Area - Wahyuningrum, Catur Ayu; Wulandari, Dyah Ari; Suripin, Suripin; Pratama, Alfyan Amar; Sari, Yunitta Chandra; Baihaqi, Fajar Andi (Universitas Diponegoro, 2025)
Landslides are among the most unpredictable and destructive sediment-related disasters, especially in mountainous regions with complex terrain and limited field accessibility. In 2004, a catastrophic landslide from the Mount Bawakaraeng Caldera delivered more than 100 million cubic meters (MCM) of sediment into the Bili-Bili Reservoir, filling its dead storage and threatening its long-term functionality. his study uses Sentinel-1A satellite imagery and Differential Interferometric Synthetic Aperture Radar (DInSAR) to perform a rapid, spatially driven assessment of landslide hazards in the Bili-Bili Reservoir Catchment Area. The results reveal surface deformation of up to ±1.55 meters, concentrated in upstream zones. High-risk areas span 71.00 km², with an estimated mobilizable volume of 110.04 MCM and a potential sediment yield of 27.14 MCM per year, nearly equal to the reservoir’s dead storage. To mitigate this threat, the study proposes an integrated mitigation framework. Structural interventions include rehabilitating existing sediment control systems and constructing new sabo dams. Non-structural strategies such as slope revegetation and bioengineering are also recommended. This study demonstrates how remote sensing can identify subtle ground deformation and provides actionable insights for safeguarding critical water infrastructure in sediment-prone tropical watersheds.